فاعلية برنامج إرشاد جمعي في تحسين مستوى التكيف لدى طلبة صعوبات التعلم بسلطنة عمان - Hishomudin Ahmad; Ayad Najeeb Abdullah Al Obaidi; Naser Saeid Mubarak al-Tubi (Persatuan Bekas Mahasiswa Islam Timur (PBMITT), 2024)
Non-Indexed Publication